2020
DOI: 10.1002/jbm.a.37026
|View full text |Cite
|
Sign up to set email alerts
|

New antiglaucomatous agent for the treatment of open angle glaucoma: Polymeric inserts for drug release and in vitro and in vivo study

Abstract: A benzamidine derivative from diminazene was tested for a novel activity: treatment of primary open‐angle glaucoma. This drug was incorporated into mucoadhesive polymeric inserts prepared using chitosan (Chs) and chondroitin sulfate (CS). Of current interest is the mucoadhesion, which increases the contact time with the ocular surface, resulting in improved bioavailability; also, the inserts are made to act as a prolonged release system. In the present work the inserts were prepared by the solvent casting meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Mucoadhesive polymeric inserts prepared using CH and chondroitin sulfate were used as DDSs for benzamidine in the research of Cesar et al This study showed promising results for anti-glaucoma treatment [57].…”
Section: Natural Biomaterials In Drug Delivery Systems (Ddss)mentioning
confidence: 99%
“…Mucoadhesive polymeric inserts prepared using CH and chondroitin sulfate were used as DDSs for benzamidine in the research of Cesar et al This study showed promising results for anti-glaucoma treatment [57].…”
Section: Natural Biomaterials In Drug Delivery Systems (Ddss)mentioning
confidence: 99%
“…Several studies have used chitosan, a highly biodegradable polymer, to develop ocular inserts and films for topical delivery. Modifications were carried out to improve the solubility of chitosan, such as the addition of chondroitin sulfate and hydroxyethyl cellulose [ 65 , 66 ]; these modified chitosan inserts were able to lower IOP by delivering 4-aminodiphenylamine (a benzamidine derivative) and dorzolamide, respectively. Interestingly, with a sustained release, both drugs also exhibited a neuroprotective effect towards the retinal ganglion cells (RGC).…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…Okuläre Inserte nur mit CS werden für verschiedene Wirkstoffe zur Glaukombehandlung entwickelt, z.B. für Bimatoprost [212], Brimonidintartarat [213] und Diminazen [214], außerdem in Kombination mit Hydroxyethylcellulose für Dorzolamid [215] und in Kombination zu gleichen Teilen mit Chondroitinsulfat für Diminazen [216].…”
Section: Neuartige Wirkstoffabgabesystemeunclassified